The feeding habits of the Amur whitefish Coregonus ussuriensis in the Amur River, China - Wang, Jilong; Huo, Tangbin; Li, Peilun; Lu, Wanqiao (Frontiers in Environmental Science, 2023)
Abstract：In order to study the feeding habits, samples of Coregonus ussuriensis were collected seasonally in the Amur River, China. A total of 574 samples were collected, including 200 individuals with empty stomach. The stomach contents of the remaining 374 samples were identified, counted, weighed, and analyzed for the next step. The results showed that the vacuity rate of Coregonus ussuriensis was 34.84% in total, rates in summer and autumn were higher than spring and winter. Prey items can be divided into three categories: fish, benthos, and mammals, with 62 taxonomic units. Among them, fish have the highest relative importance index (IRI), followed by benthos, and mammals. Specifically, Exopalaemon modestus is the dominant species among the food species of Coregonus ussuriensis, and the unidentified fish, Hydropsyche sp., Hemiculter leucisculus, Abbottina rivularis, and Saurogobio dabryi are important species. The average repletion index (RI, %) of Coregonus ussuriensis is the highest in autumn (1.86), followed by winter (1.40), summer (1.26), and spring (1.02). The main food of Coregonus ussuriensis is benthos in spring and autumn, while fish in summer and winter. Cluster analysis showed that, according to the similarity level of bait biological composition, the fork length group samples of Coregonus ussuriensis could be divided into three groups: 210-330mm, 330-450mm and >450mm. The highest IRI% of feed organisms in these three groups of samples were fish (73.67%), benthos (75.12%), and benthos (94.46%), respectively. It can be seen that with the growth of the fork length of Coregonus ussuriensis, the importance of benthos in its diet increases. The results of the RDA analysis on the relationship between main bait organisms and factors indicated that season, river level, river width, and fish size have a significant impact on bait organisms, and have a positive or negative impact on the quality scores of some bait species. This study filled the gap of biological research on feeding ecology of Coregonus ussuriensis, and would lay a research foundation for its ecological research, resource protection and aquaculture.